Baricitinib for the treatment of severe alopecia areata: results from a 52-week multicenter retrospective real-world study - Carlo A. Vignoli; Luigi Gargiulo; Luciano Ibba; Anna Balato; Mauro Barbareschi; Stefania Barruscotti; Giulia Bazzacco; Francesco Bellinato; Vittoria G. Bianchi; Valeria Boccaletti; Raffaele D. Caposiena Caro; Silvia M. Ferrucci; et al. (Journal of Dermatological Treatment)
Purpose of the article: Baricitinib, a JAK 1/2 inhibitor, is approved for treating severe alopecia areata (AA). This study aimed to evaluate the long-term effectiveness and safety of baricitinib in a real-world setting over 52 weeks.Materials and methods: This multicenter retrospective study included 96 adult patients diagnosed with severe AA from 11 Italian Dermatology Units. All patients received 4 mg of baricitinib daily. Effectiveness was assessed using the Severity of Alopecia Tool (SALT) score, with the primary endpoint defined as achieving a SALT score ≤ 20 at week 52. Secondary endpoints included achieving a Clinician-Reported Outcome (ClinRO) score of 0 or 1 for eyebrow (ClinRO EB) and eyelash hair loss (ClinRO EL), with a ≥ 2-point improvement from baseline.Results: After 52 weeks, 61.5% of patients achieved a SALT score ≤ 20. Additionally, 67.6% and 69.7% of patients attained ClinRO EB and ClinRO EL scores of 0 or 1, respectively, with a ≥ 2-point improvement. No significant adverse safety events were reported during the study.Conclusions: The study confirms the long-term effectiveness and safety of baricitinib for severe AA in a real-world setting. These findings align with clinical trial results and reinforce baricitinib’s role as a viable treatment option for severe AA.